A System Engineering Approach to Sustainability Decision Support System Based on the Global Reporting Invitiative - Syaukani, Muhammad (Infact: International Journal of Computers, 2025)
Study this to develop a Sustainability Decision Support System (SDSS) based on the Global Reporting Initiative (GRI) at Insitut Teknologi Bisnis dan Bahasa Dian Cipta Cendikia (ITBA DCC) using a systems engineering approach. SDSS is designed to support decision-making sustainability data through a staged engineering system that includes analysis requirements, design, implementation, testing, application, and maintenance. This system integrates GRI indicators with campus data and produces visualizations as well as multi-criteria analysis, using increased transparency and accountability within institutions. The results show that SDSS is capable of facilitating comprehensive reporting in dimensions of social, economic, environmental, and governance. Research also confirms the importance of stakeholder collaboration in designing a responsive system to challenge sustainability in college high. The developed model is expected to be replicated in other institutions to strengthen digital governance? sustainability and standardization.